2007
DOI: 10.1002/bjs.5816
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre randomized clinical trial of mechanical bowel preparation in elective colonic resection

Abstract: ISRCTN28535118 (http://www.controlled-trials.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(155 citation statements)
references
References 40 publications
5
143
2
5
Order By: Relevance
“…However, a large multicenter study and a review conducted by the Cochrane Collaboration found that there was no difference in the fistula rate or severity of infectious complications when comparing a group that used mechanical bowel preparation and another group that did not use it (23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…However, a large multicenter study and a review conducted by the Cochrane Collaboration found that there was no difference in the fistula rate or severity of infectious complications when comparing a group that used mechanical bowel preparation and another group that did not use it (23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…Bowel preparation is known potentially to cause significant fluid shifts that may result in dehydration and electrolyte deficiencies. 30 Two RCTs have shown no benefit with the routine use of bowel preparation in elective colorectal surgery 31,32 with another suggesting an increased risk of postoperative anastomotic breakdown. 33 The evidence for avoiding routine nasogastric tube decompression and implementation of epidural anaesthesia postoperatively has been ratified by meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical bowel preparation contributes to preoperative dehydration and is unpleasant for the patient. 5,6 Recent evidence suggests that MBP does not decrease anastomotic leakage, wound infection, or mortality (for the majority of patients), 7 and it may even have a tendency towards a higher incidence of spillage of bowel contents due to formed stool being replaced by liquid bowel contents. 8 The patient population in which MBP is indicated is still a matter of debate amongst surgeons, and it is often given for ''handling'' reasons, with some surgeons arguing that MBP facilitates easier laparoscopic surgery.…”
Section: Preoperative Fluid Managementmentioning
confidence: 99%